The Development of Turnover Intention Prediction Model for Out-of-Office Workers in Thailand - Maneechaeye, Pattarachat (Journal of Multidisciplinary in Social Sciences, 2023)
The study of the development of turnover intention prediction model for out-of-office workers in Thailand aims to investigate the factors affecting probability of turnover intention and to develop the most suitable turnover intention prediction model for out-of-office workers by using binary logistic regression approach. This is a quantitative social science survey research. The population of the study are professional employees that are assigned to work outside the office, including but not limited to salespersons, financial auditors, management consultants, medical representatives, real estate agents and other professional jobs that often work outside an office. Research tools are questionnaires and rating scales. A convenience sampling method was applied. Self-administrative questionnaires both hard copy and electronic form were directly distributed to various out-of-office workers in Thailand. In this study, 420 sample size was collected and separate into 67% of training set and 33% of test set. The well-fitted turnover intention prediction from binary logistic regression approach for out-of-office worker can be deliberately developed and fitted with empirical data. It is obvious and clear that all thelegacy negative work-related factors are still relevant and contribute to the prediction of turnover intention of employees. Organizations should utilize any possible countermeasures to mitigate these risks. For future research, qualitative research should be done so as to gain more insights regarding turnover intention.